EDUKASI JAJANAN SEHAT SEBAGAI UPAYA PENCEGAHAN STUNTING PADA ANAK USIA PRASEKOLAH - Kelrey, Fathimah; Mars Clara liem, Glorya; Mahel Sari Sangga (Institut Citra Internasional, 2024)
Healthy snacks are part of safe, nutritious food that plays an important role in growth and preventing stunting. The incidence of stunting in toddlers including preschool children in Indonesia is still quite high so it needs to be prevented because it is at risk of lack of optimal nutritional fulfillment. To overcome this, health education is needed regarding healthy snacks. The purpose of this activity is to ensure that preschool children have an understanding of healthy snacks from an early age. The educational methods used in this community service are lectures, discussions, questions and answers and using flipchart media. The results of this activity show an increase in knowledge from participants about healthy snacks in preschool children at Angasa Kindergarten, Pattimura Air Force Base, Ambon, as evidenced by children being able to choose or distinguish between healthy and unhealthy snacks. The conclusion of this activity is that healthy snack education for preschool children through health counseling can increase children's knowledge about healthy snacks.